Pendidikan Kesehatan tentang Pre Eklamsi Penting untuk Pengetahuan Ibu Hamil dalam Persiapan Menghadapi Komplikasi - Winancy Winancy (Poltekkes Kemenkes Palu, 2019)
Preeclampsia is one of the direct causes of maternal death, the incidence of preeclampsia initially does not provide symptoms and signs, but at one time it can deteriorate rapidly, so it needs a series of examinations, detection, and identification of risk factors and controls so that it is possible to do complex primary prevention. This disease is closely related to the factors of age, parity and history of hypertension, so the alertness of pregnant women and their families in early detection of complications of pregnancy plays an important role. This study aims to determine the effect of health education about pre-eclampsia on knowledge, attitudes, and preparation for coping with labor complications in pregnant women in the health center of Tapos Depok sub-district in 2017. This study was a quasi-experimental study with a pre-test and posttest design. The sample in this study were pregnant women who examined their pregnancies at the Tapos Sub-District Health Center at the time of data collection as many as 60 respondents who were divided into two groups and taken by accidental sampling. Respondents were divided into 2 groups, namely those who were given health education with leaflet and multimedia media. Data analysis was done by univariate and bivariate with Wilcoxon and Mann Whitney tests. The results showed that there was an effect of health education about pre-eclampsia on the increase in knowledge and attitudes of pregnant women, but did not affect the preparation of pregnant women in preparation for complications of labor. Health education using multimedia is more able to increase respondents' knowledge and attitudes about pre-eclampsia compared to health education with leaflet media